2018
DOI: 10.1088/1741-4326/aae8bc
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and simulation studies on gold bubble movement in gas-filled hohlraums

et al.

Abstract: A recent experiment on the Shenguang III laser facility has applied open-end gold hohlraums with two gas pressures to study the movement of a plasma bubble. Under a laser intensity and width close to those of an ignition main pulse, the bubbles possess radial scales from several hundred to one thousand micrometers. An x-ray framing camera is used to measure the N-band x-ray images generated from the gold bubble plasma at different moments, from which the edge positions of the expanding bubbles are accurately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…So, it is of practical importance to study the movement of the LEH and bubble plasmas. In our previous research [19], we have observed the bubble movement in a simple open-end hohlraum. However, all of the previous works measure the boundary of the LEH and bubble plasmas with Static X-ray Imager or Gated X-ray Imager.…”
Section: Jinst 17 P11008mentioning
confidence: 99%
“…So, it is of practical importance to study the movement of the LEH and bubble plasmas. In our previous research [19], we have observed the bubble movement in a simple open-end hohlraum. However, all of the previous works measure the boundary of the LEH and bubble plasmas with Static X-ray Imager or Gated X-ray Imager.…”
Section: Jinst 17 P11008mentioning
confidence: 99%
“…According to the conditions in the Au bubble experiment conducted on the hundreds of kJ laser facility [43][44][45], we get g b,g ≈90.…”
Section: Scaling Law Of Au Bubble Velocitymentioning
confidence: 99%
“…The experiments were conducted on the hundreds of kJ laser facility in China [43][44][45][47][48][49][50]. As shown in the figure 1, all the 32 laser beams of the outer cone with a total energy of 80.9 kJ and 3 ns flat-topped pulse, entered a hollow gold hohlraum (2.8 mm diameter and 2.08 mm length), which was filled with C 5 H 12 of 1.28 mg cc −1 .…”
Section: Model Validation With Experimentsmentioning
confidence: 99%
“…Plasma collision is a Universe phenomenon widely existing in High Energy Density Physics (HEDP) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17], laboratorybased astrophysics [2,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], and Inertial Confinement Fusion (ICF) projects [37]. Since rich dynamic physics exist during the colliding process, a series of different configurations have been proposed by multi-beam laser-plasma interactions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is quite different in ICF physics that strong colliding processes occur more frequently. Especially, for the indirect-drive configuration where multi-laser beams are used to injected into a high-Z material hohlraum (gold or uranium) to provide an x-ray radiation source [37,39], plasma plumes from different focal spots of lasers will expand and collide with each other. There has been some previous work showing that bright x-ray radiations were produced during the plume colliding [37] It reveals that the local plasma evolution is complex and inhomogeneous in space.…”
Section: Introductionmentioning
confidence: 99%